DISCOURSE OF HIZBUT TAHRIR INDONESIA'S RADICALISM: A CRITICAL DISCOURSE ANALYSIS ON TEMPO.CO MEDIA - Sarmadan Sarmadan; Aceng Rahmat; Siti Gomo Attas (English Education Department, 2022)
Hizbut Tahrir Indonesia (HTI) radicalism discourse invites polemics and pros and cons that have not ended. The various perspectives on the existence until the dissolution of the mass organization need to be understood in depth, objectively, and comprehensively. This research was conducted with the aim of comprehensively dissecting the discourse of HTI radicalism which wants to substitute the Pancasila ideology by carrying the caliphate ideology. This research is a literature study using a qualitative approach. The knife of analysis is the critical discourse analysis of Norman Fairclough's model which consists of three dimensions of analysis, namely text analysis, discourse practice, and sociocultural practice. The data in this study are texts in the form of vocabulary, sentences, or discourses whose corpus is from a news story entitled